2009
DOI: 10.1111/igc.0b013e3181a8407e
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and Vinorelbine Combination in Platinum-Sensitive Recurrent Ovarian Cancer

Abstract: Gemcitabine and vinorelbine combination is effective and well tolerated in recurrent platinum-sensitive ovarian cancer. It may represent an option in the management of these patients because the chronic nature of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, most pancreatic cancer patients will exhibit disease progression and treatment provides only a slight survival advantage. Gemcitabine also has activity against other cancers including lymphomas and solid tumors such as lung, bladder and ovarian cancer [7][8][9][10].…”
Section: Gemcitabinementioning
confidence: 99%
“…However, most pancreatic cancer patients will exhibit disease progression and treatment provides only a slight survival advantage. Gemcitabine also has activity against other cancers including lymphomas and solid tumors such as lung, bladder and ovarian cancer [7][8][9][10].…”
Section: Gemcitabinementioning
confidence: 99%
“…These substances, alone or in combination, achieve a wide range of response rates. For example, Ferrero et al described a response rate of 49% with gemcitabine and vinorelbine in platinum-sensitive patients [5], whereas Burger et al found a response rate of 29% in a mixed resistant-sensitive population [6]. Lower response rates are seen among platinum-resistant patients with response rates of 25% [7], 21% [8], 11% [9], and even 3% [10] with doxorubicin and gemcitabine, topotecan and oxaliplatin, gemcitabine and vinorelbine, and vinorelbine in various combinations and dosages, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A number of chemotherapeutic agents are active in recurrent ovarian cancer including a combination of platinum and paclitaxel (Gonzalez-Martin 2003; Parmar 2003). Other chemotherapeutic agents with activity in recurrent ovarian cancer include topotecan, gemcitabine, Caelyx, Etoposide, Doxocycline, Docetaxel, Oxaliplatin and Bevacisamab (Avastin) (Bookman 1998; Ferrero 2009; Markman 2004; Monk 2009; Weber 2009). Newer chemotherapeutic agents have shown activity in recurrent ovarian cancer and response rates of 20 to 30% have been described (Harter 2006; Selinger 2009; Ozols 2005; Wright 2006).…”
Section: Introductionmentioning
confidence: 99%